Mnenje vzgojiteljic in vzgojiteljev o kompetentnosti za vodenje gibalnih dejavnosti predšolskih otrok, upoštevajoč lastno gibalno dejavnost - Plevnik, Matej (Revija za elementarno izobraževanje, 2021)
The opinion of preschool teachers on their self-perceived competence for leading the physical activity process in preschool children in relation to their own leisure-time physical activity. The purpose of the study was to determine whether the regular leisure-time physical activity of preschool teachers (n = 177) is associated with their self-perceived competence for leading physical activities among preschool children. For the data collection on self-assessed physical activity and the subjective assessment of competence for leading the process of physical activities among preschool children, we used a questionnaire. We can conclude that the leisure-time physical activity of preschool teachers is associated with their subjectiveperception of competence for leading the process of physical activity among preschool children.
Keywords: preschool period, kindergarten, motor development, motor skill, competency; preschool period; kindergarten; motor development; motor skill; competency